Is human capital a major determinant for foreign investors? Comparative study between India and Romania - Laura Diaconu; Andrei Maxim (CES Working Papers, 2019)
The economic literature of the twenty-first century stresses the idea according to which achieving a certain level of human capital is one of the main preconditions for a country to attract and maintain foreign investors, particularly the ones seeking to improve the efficiency of their activities. Therefore, the main aim of the paper is to analyse if human capital represents a major determinant in attracting the foreign investors in two emerging economies - Romania and India. In order to reach this objective, two qualitative methods were used: the documentary research and the in-depth interview, conducted on the managers/experts from eleven multinational companies, which are present in both countries. The results of the study underline that the level of education and the skills of the potential employees have become increasingly important drivers of foreign investments in both India and in Romania, even if the leading determinant still remains the low cost of production.
Keywords: 330; human capital; foreign direct investment; multinational companies; India; Romania